2021
DOI: 10.3390/antiox10101602
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Linked Organ Lipid Hydroperoxidation and Dysregulation in Mouse Model of Nonalcoholic Steatohepatitis: Revealed by Lipidomic Profiling of Liver and Kidney

Abstract: Nonalcoholic steatohepatitis (NASH) is a prevalent disease related to lipid metabolism disorder and oxidative stress. Lipid hydroperoxidation is known to be a critical driving force of various disorders and diseases. However, the combination of both intact and hydroperoxidized lipids in NASH has not yet been studied. In this work, the liver and kidney samples from NASH-model mice were comprehensively investigated by using the LC/MS-based lipidomic analysis. As a result, triglycerides showed the amount accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…While there has been a report on LD accumulation induced by oxidative stress in NAFLD [ 51 ], studies on the oxidative stress-related LD alteration in CKD are quite limited, particularly for the LD oxidation. Lipid hydroperoxides are known to connect with the vicious circle of abnormal lipid metabolism and energy production disturbance [ 17 ], yet, to the best of our knowledge, this is the first study to reveal lipid peroxidation in LDs from kidney cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there has been a report on LD accumulation induced by oxidative stress in NAFLD [ 51 ], studies on the oxidative stress-related LD alteration in CKD are quite limited, particularly for the LD oxidation. Lipid hydroperoxides are known to connect with the vicious circle of abnormal lipid metabolism and energy production disturbance [ 17 ], yet, to the best of our knowledge, this is the first study to reveal lipid peroxidation in LDs from kidney cells.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress is one of the most vital factors in the development of CKD. The overproduced reactive oxygen species (ROS), as well as the inefficient antioxidant system, result in the imbalanced redox, which has been known to be associated with various pathological conditions and non-infectious chronic diseases, especially metabolic diseases, such as nonalcoholic fatty liver disease (NAFLD), type two diabetes, and CKD [ 16 , 17 , 18 ]. In cells, oxidative stress is commonly associated with damage to DNA, proteins, lipids, and other physiological molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The semi-quantitative analysis of the cellular lipids was performed using a Prominence HPLC system (Shimadzu Corp., Kyoto, Japan) coupled to an LTQ Orbitrap mass spectrometer. The conditions were according to our previous work [ 23 ]. In brief, an Atlantis T3 C18 column (2.1 mm × 150 mm, 3 µm; Waters, Milford, MA, USA) was employed for chromatographic separation, and the electrospray ionization (ESI) source in both positive and negative modes was equipped for detection.…”
Section: Methodsmentioning
confidence: 99%
“…The MS/MS fragmentation was performed using collision-induced dissociation (CID) by data-dependent acquisition. For raw data processing, Xcalibur 2.3 (Thermo Fisher Scientific) was used with the help of the LIPIDMAPS database ( , accessed on 12 February 2022) and our in-house library [ 23 ]. The lipid data were normalized by total protein level, which was determined using the Pierce BCA Protein Assay Kit (Thermo Fisher Scientific), and the final results are presented as relative amounts to the control group.…”
Section: Methodsmentioning
confidence: 99%
“…Simple steatosis can progress to NASH, cirrhosis and hepatocellular carcinoma owing to multiple factors, including oxidative stress and insulin resistance [ 10 ]. Lipidomic studies revealed an increase in lipid hydroperoxides in both in vitro (lipid droplets from fatty-acid-supplemented hepatocytes) and in vivo (liver of diet-induced mice) studies [ 11 , 12 ]. Therefore, fatty liver may be a potential risk factor for NASH progression and should be prevented.…”
Section: Introductionmentioning
confidence: 99%